“Not try to save them or ask them to breathe through their oppression”: Educator perceptions and the need for a human-centered, liberatory approach to social and emotional learning - Lin, Meiko; Olsen, Svea; Simmons, Dena N.; Miller, Miriam; Tominey, Shauna L. (Frontiers in Education, 2023)
Social and emotional learning (SEL) has been identified as one approach to promote positive mental health outcomes while alleviating the stressors of systemic racism and a global pandemic. As the United States turns to SEL as a remedy for mental health challenges and the current civil unrest, it becomes increasingly relevant to understand what SEL means to those who use it the most to strengthen the implementation of current programs as well as to inform the development of new programs to fill existing gaps. This qualitative study expands prior research by exploring how in-service educators define SEL (N=427). Our findings highlight that educators perceive SEL as more expansive than current competency-based models. Educators describe SEL as a praxis that can be responsive to student and community needs, facilitate healing, and center humanity along with racial and social justice. We discuss implications that highlight the potential risks and harm that can be perpetuated by the current practice of SEL and, like the educators in our study, advocate for dismantling white supremacy structures in education through the co-creation of a humanizing SEL approach.